Phonological Patterns and Processes: A Literature Review - Bima Bahari; Sitanggang, Cansa Namira; Hafizah Ismayati; Yani Lubis (Indonesian Journal of Multidisciplinary Scientific Studies, 2023)
This article examines various phonological patterns and processes, providing an overview of the current understanding and research in the field of phonology. This article aims to provide an overview of the current understanding and research in phonology by conducting a comprehensive analysis of relevant scholarly articles, books, and research papers. It explores fundamental concepts such as phonemes, allophones, and distinctive features, and delves into the study of phonological processes such as assimilation, dissimilation, and vowel harmony. This article is non-research type and involves literature review that takes research sources from experts and then collects these sources in one article. The review begins by exploring the fundamental concepts of phonology, such as phonemes, allophones, and distinctive features. It discusses different phonological processes, including assimilation, dissimilation, and vowel harmony, and their role in shaping the sound patterns of languages. It also explores studies that analyze how students acquire the phonological systems of their native language and the role of phonological awareness in reading and spelling skills. In addition, the review addresses the impact of phonological processes on second language acquisition and the challenges faced by EFL learners and talks about the importance of phonology in sociolinguistic contexts. This literature review provides a comprehensive overview of phonological patterns and processes, highlighting their significance in understanding language structure, acquisition, and sociolinguistic variation.